Enhancement of Lignin Biopolymer Isolation from Hybrid Poplar by Organosolv Pretreatments. (28th August 2014) - Wu, Miao; Pang, Jinhui; Zhang, Xueming; Sun, Runcang
Abstract : Lignocellulosic biomass is an abundant renewable resource that has the potential to displace petroleum in the production of biomaterials and biofuels. In the present study, the fractionation of different lignin biopolymers from hybrid poplar based on organosolv pretreatments using 80% aqueous methanol, ethanol, 1-propanol, and 1-butanol at 220°C for 30 min was investigated. The isolated lignin fractions were characterized by Fourier transform infrared spectroscopy (FT-IR), high-performance anion exchange chromatography (HPAEC), 2D nuclear magnetic resonance (2D NMR), and thermogravimetric analysis (TGA). The results showed that the lignin fraction obtained with aqueous ethanol (EOL) possessed the highest yield and the strongest thermal stability compared with other lignin fractions. In addition, other lignin fractions were almost absent of neutral sugars (1.16–1.46%) though lignin preparation extracted with 1-butanol (BOL) was incongruent (7.53%). 2D HSQC spectra analysis revealed that the four lignin fractions mainly consisted of β - O -4′ linkages combined with small amounts of β -β ′ and β -5′ linkages. Furthermore, substitution of C α in β - O -4′ substructures had occurred due to the effects of dissolvent during the autocatalyzed alcohol organosolv pretreatments. Therefore, aqueous ethanol was found to be the most promising alcoholic organic solvent compared with other alcohols to be used in noncatalyzed processes for the pretreatment of lignocellulosic biomass in biorefinery.